Factors Affecting Runners’ Continuance Intention on Strava Running Apps Usage In Jakarta - Soesilo, Ferdinandus Winandy; Hendharta, Cecelia Suprapti (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to analyze the influence of perceived ease of use, perceived usefulness, and social influence on the continuance intention to use the Smart running application (Case Study: Strava App Users in Jakarta). A survey of 110 respondents (54.55% male, 45.45% female) was conducted, with the dominant age range being 31-40 years (35.45%) and professions primarily private employees (28.18%) and entrepreneurs (24.55%). Data were analyzed using SmartPLS 3.0, including validity, reliability, determination, and significance tests. The results show that perceived ease of use and social influence significantly influence continuance intention, while perceived usefulness does not significantly influence it. The independent variables explain 41% of the variance in continuance intention. Future research is advised to expand the number of respondents, geographical area, and examine other variables such as word-of-mouth marketing or brand awareness.